EXPERIENTIAL LEARNING AT A DAIRY FARM (A STUDY ON EARLY CHILDHOOD LIFE SCIENCE KNOWLEDGE) - Dzikriyanti, Riri; Hartati, Sofia; Meilanie, Sri Martini (Erudio Journal of Educational Innovation, 2025)
This study aims to explore how experiential learning on a dairy farm can enhance early childhood knowledge of life sciences, particularly regarding the life cycle of dairy cows, milk production processes, and dairy-based products. A qualitative descriptive approach was employed to provide an in-depth understanding of children's learning experiences during their interaction with the farm environment. The research was conducted at the Cibugary Dairy Farm in Jakarta, Indonesia, involving early childhood participants who engaged in hands-on educational activities. Data were collected through participant observation, interviews with children, educators, and parents, as well as documentation analysis.The results demonstrate that direct engagement in activities such as feeding cows, observing the milking process, and learning about dairy product processing significantly improved children's understanding of life science concepts. Children not only recognized the origins of milk but also gained insights into sustainable farming practices and the importance of animal welfare. Experiential learning also fostered curiosity, critical thinking skills, and a positive attitude toward science. Parents and educators observed that children began to ask more questions about food sources and showed increased interest in choosing healthier dietary options.This study highlights the effectiveness of experiential learning in providing meaningful educational experiences for young learners. It underscores the importance of integrating hands-on activities into early childhood education to support cognitive and affective development while instilling environmental awareness and empathy for animals.